EFEKTIVITAS PEMBERIAN SMOOTHIES KOMBINASI ANEKA BUAH DAN SAYUR TERHADAP PERUBAHAN TEKANAN DARAH PADA WANITA DEWASA - Ina Mutma’inah; Mohammad Jaelani; Cahyo Hunandar (Poltekkes Kemenkes Semarang, 2018)
Background : Hypertension is a long term condition in which blood pressure is higher than 140/90 mmHg. Antihypertensive drugs therapy took a long time and caused side effects so that further treatment is needed through non-pharmalogycal therapy such as the consumption of smoothies combination of various fruits and vegetables that contain high fiber and potassium.Objective : To determine the effectiveness of smoothies combination of various fruits and vegetables consumtion to changes in blood pressure change in adult women.Method : This research is a true experiment with Randomized Pre and Post Test Control Group Design. Sampling was done randomly to get 30 samples. Data collection were included by age, nutritional status, occupation, blood pressure data before and after treatment and fiber, sodium, potassium, calcium and magnesium intakes.Results : There was an effect of smoothies combination of various fruits and vegetables consumtion to decrease cytolic and diastolic blood pressure during the study with confounding variables of fiber, sodium, potassium and magnesium intake (p = 0.025 and p = 0.037).Conclusion : The average systolic and diastolic blood pressure in the treatment group were decreased after consumtion smoothies combination of various fruits and vegetables, while the control group tended to increased because they were not consume smoothies.